Evaluation of diagnostic efficacy of multimode ultrasound in BI-RADS 4 breast neoplasms and establishment of a predictive model - Chen, Yunhao; Lu, Juerong; Li, Jie; Liao, Jingtang; Huang, Xinyue; Zhang, Bo (Frontiers in Oncology, 2022)
Abstract: Objectives: To explore the diagnostic efficacy of US, 2-Dimensional and 3-Dimensional Shear-wave elastography (2D-SWE and 3D-SWE) and Contrast-enhanced ultrasound (CEUS) in breast neoplasms in category 4 based on the Breast Imaging Reporting and Data System (BI-RADS) from the American College of Radiology (ACR). And to develop a risk-prediction nomogram based on the optimal combination so as to provide a reference for clinical management of BI-RADS 4 breast neoplasms. Methods: From September 2021 to April 2022, a total of 104 breast neoplasms categorized as BI-RADS 4 by Ultrasound (US) were included in this prospective study. There were 78 breast neoplasms randomly assigned into the training cohort; the area under the receiver-operating-characteristic curve (AUC), 95% confidence interval (95%CI), sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 2D-SWE, 3D-SWE, CEUS and their combination were analyzed and compared. The optimal combination was selected to develop a risk-prediction nomogram. The performance of the nomogram was assessed by a validation cohort of 26 neoplasms. Results: Of the 78 neoplasms in the training cohort, 16 were malignant and 62 were benign. Among the 26 neoplasms in the validation cohort, 6 were malignant and 20 were benign. The AUC values of 2D-SWE, 3D-SWE and CEUS with no significant difference. After the comparison of different combinations, 2D-SWE+CEUS showed the optimal performance. Least absolute shrinkage and selection operator (LASSO) regression was used to filter the variables in this combination, and the variables included Emax, Eratio, enhancement mode, perfusion defect and area ratio. Then a risk-prediction nomogram with BI-RADS was built. The performance of the nomogram was better than that of radiologists in the training cohort (AUC: 0.974 vs. 0.863). In the validation cohort, there was no significant difference in diagnostic accuracy between the nomogram and experienced radiologists (AUC: 0.946 vs. 0.842). Conclusions: US, 2D-SWE, 3D-SWE, CEUS and their combination could improve the diagnostic efficiency of BI-RADS 4 breast neoplasms. The diagnostic efficacy of US+3D-SWE was not better than US+2D-SWE. US+2D-SWE+CEUS showed the optimal diagnostic performce. The nomogram based on US+2D-SWE+CEUS performs well.